Ophthalmology case - Fernandes, Alexandra; Madureira, Cristina; Pinto, Fátima (BIRTH AND GROWTH MEDICAL JOURNAL, 2018)
Brown syndrome is a rare ocular motility abnormality characterized by a restriction of the superior oblique tendon, which results in a restriction of elevation in adduction. This entity can be congenital or acquired. The cause of congenital Brown`s syndrome remains unknown but some cases with a family history have been described. Spontaneous resolution occurs between 20 to 30%. We describe a case of an eight-year-old boy with congenital Brown syndrome.